15 Exploring the use of innovative technology to deliver junior doctors induction at the hospice. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Seaman, Siwan; Evans, Rebecca; Taubert, Mark
Abstract : Background: There is a paucity of published evidence evaluating the effectiveness of induction methods for trainee doctors. In any 12 month period 17 trainees (3 foundation doctors, 8 core medical trainees and 6 specialty trainees) will rotate through our hospice, resulting in the medical induction programme being repeated at least 8 times per year. Methods: Considering prudent healthcare principles, the aim was to evaluate the current induction programme and to scope alternative, more efficient delivery methods. Feedback on the induction of 16 trainees was analysed in addition to feedback from 29 medical students who had experienced virtual reality (VR) palliative care teaching methods locally as well as an online survey sent to 33 previous trainees at the hospice to ascertain their views on alternative delivery methods. Results: Amongst the cohort who had experienced VR, the feedback was generally positive. There was however a general reluctance to consider new techniques amongst past trainees of the hospice who, unanimously, valued the face-to-face induction they had received, this is consistent with positive GMC trainee survey responses at the hospice to the induction question. Discussion and conclusion: There was not enough evidence from this work to suggest a switch, with the associated resource costs, to deliver the induction programme from face-to-face to VR or other pre-recorded media. However, given the positive response from students who had previously experienced VR, we have created a 360 degree tour of the hospice and induction programme to pilot using equipment on loan and evaluate its acceptability and effectiveness as a delivery method of induction at the hospice.